Distal femoral deformity correction by percutaneous open-wedge osteotomy and a simplified external fixation technique: a retrospective case series. Issue 3 (May 2020) - Atef, Ashraf; El-Rosasy, Mahmoud; El-Gebaly, Osama
Abstract : Background: Varus and valgus distal femoral malalignments increase medial and lateral loads of the knee respectively. Early femoral realignment osteotomy reduces symptoms and may prevent joint degeneration. Several osteotomy techniques and fixation methods have been described to maintain such corrective osteotomy. There is little evidence supporting the choice of one technique over the other for correction of distal femoral deformities. The aims of this study were to determine if a minimally invasive external fixation technique could correct deformity and report treatment-related complications. Methods: Fifty-two limbs in 30 patients presented with distal femoral deformities due to different etiologies. The patients underwent minimally invasive external fixation techniques with a minimum 2-year follow-up. Their ages ranged from 14 to 24 years (average 20.8 years). Limb length discrepancy (LLD) was present in eight patients and ranged from 4 to 8 cm (average 5.4 cm). The deformity was valgus in 38 limbs and varus in 14 limbs. Results: All osteotomies united successfully after an average 5.2 months, and the external fixation index was an average of 1.1 months/cm. None of the patients had residual deformity or LLD. All patients reported a satisfactory outcome except two patients who had loss of the last 10 degrees of knee flexion. Superficial pin track infection occurred in all patients, but no nerve or vascular injuries or deep infections occurred. Conclusions: The distal femoral osteotomy (DFO) with a unilateral Ilizarov fixator modification is an entirely percutaneous procedure that has less risk of primary or secondary loss of correction. Stability of the construct allows early mobilization. Level of Evidence: Level IV.